2004
DOI: 10.1103/physreve.70.016116
|View full text |Cite
|
Sign up to set email alerts
|

Survival probabilities in time-dependent random walks

Abstract: We analyze the dynamics of random walks in which the jumping probabilities are periodic timedependent functions. In particular, we determine the survival probability of biased walkers who are drifted towards an absorbing boundary. The typical life-time of the walkers is found to decrease with an increment of the oscillation amplitude of the jumping probabilities. We discuss the applicability of the results in the context of complex adaptive systems.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 25 publications
3
43
1
Order By: Relevance
“…The low value of E p may suggest that it belongs to the long-duration class; however, it is becoming clear that hardness cannot be used to reliably distinguish between the two classes (for further discussion see Nakar 2007). Similarly, while the negative lag inferred for XRF 050416a may suggest an SHB classification, examples do exist of long-duration BATSE bursts with negative lags (Norris & Bonnell 2006).…”
Section: Is Xrf 050416a a Short Burst?mentioning
confidence: 92%
“…The low value of E p may suggest that it belongs to the long-duration class; however, it is becoming clear that hardness cannot be used to reliably distinguish between the two classes (for further discussion see Nakar 2007). Similarly, while the negative lag inferred for XRF 050416a may suggest an SHB classification, examples do exist of long-duration BATSE bursts with negative lags (Norris & Bonnell 2006).…”
Section: Is Xrf 050416a a Short Burst?mentioning
confidence: 92%
“…This model also explains the [135,352] correlation, the different E iso would be due to the observer being at different angles relative to the jet axis. This hypothesis has been tested in a variety of ways [186,324,249,178]. Attempts to extend the universal θ −2 jet structure to include X-ray flashes ( §2.5), together with use of the Amati relation between the spectral peak energy E peak and E γ,iso ( §2.6), leads to the conclusion that a uniform top-hat model is preferred over a universal θ −2 jet model [250].…”
Section: Jetsmentioning
confidence: 99%
“…Indeed, Nakar & Piran (2005) have recently argued that the A02 correlation might be the result of selection effects, as a large number of GRBs (at least 50 per cent in the sample they considered) do not appear to follow it. Similar findings have been reported by Band & Preece (2005) who performed a more refined analysis and concluded that 88 per cent of BATSE bursts are not consistent with the A02 relation, and only at most 18 per cent could be consistent with it.…”
Section: Spread Of the Correlationsmentioning
confidence: 99%
“…No unique and robust interpretation of such results has been found so far (Zhang & Meszaros 2002;Schaefer 2003;Eichler & Levinson 2004;Liang, Dai & Wu 2004;Rees & Meszaros 2005). However, it is clear that if these correlations were to hold for the whole GRB population E-mail: celotti@sissa.it (see Nakar & Piran 2005;Band & Preece 2005;Friedman & Bloom 2005, for dissenting views), they could provide powerful clues to the physical origin of the prompt emission and have important repercussions on the potential cosmological use of GRBs.…”
Section: Introductionmentioning
confidence: 99%